2017
DOI: 10.1016/j.apjtm.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 targets and inhibits tumor suppressor gene PTEN to promote prostate cancer cell proliferation and invasion: An experimental study

Abstract: miR-21 can target and inhibit tumor suppressor gene PTEN expression to promote prostate cancer cell proliferation and invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 15 publications
3
45
0
Order By: Relevance
“…For this reason, our study aimed to expand the first findings in order to gain a better understanding of the tumor biology of RCC. Similarly to miR-1, miR-21 was also detected in various malignant tissues, such as prostate and lung cancer and their metastases, pancreatic cancer and colorectal cancer (17)(18)(19)(20)(21). However, in contrast to miR-1, miR-21 appears to be an oncomir.…”
mentioning
confidence: 99%
“…For this reason, our study aimed to expand the first findings in order to gain a better understanding of the tumor biology of RCC. Similarly to miR-1, miR-21 was also detected in various malignant tissues, such as prostate and lung cancer and their metastases, pancreatic cancer and colorectal cancer (17)(18)(19)(20)(21). However, in contrast to miR-1, miR-21 appears to be an oncomir.…”
mentioning
confidence: 99%
“…PC3 cells do not express PTEN; however, LNCaP do. PTEN plays a significant role during cell survival and migration signaling and inhibits PI3K/AKT, as well as the focal adhesion-related signaling axis [33][34][35]. We have found that, after miR-21 was inhibited, the colony formation of LNCaP cells were decreased, but there was no clear effect on PC3 cell colony formation.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have demonstrated that miRNAs regulate the expression of PTEN in PCa. For instance, Yang et al reported that miR‐21 increased proliferation and invasion of PCa cells by targeting PTEN . Nip et al reported that miRNA‐4534 downregulated the expression of PTEN in PCa .…”
Section: Discussionmentioning
confidence: 99%